2017
DOI: 10.1186/s12913-017-2275-3
|View full text |Cite
|
Sign up to set email alerts
|

Key aspects related to implementation of risk stratification in health care systems-the ASSEHS study

Abstract: BackgroundThe lack of proven efficacy of new healthcare interventions represents a problem for health systems globally. It is partly related to suboptimal implementation processes, leading to poor adoption of new interventions. Activation of Stratification Strategies and Results of the interventions on frail patients of Healthcare Services (ASSEHS) EU project (N° 2013 12 04) aims to study current existing health Risk Stratification (RS) strategies and tools on frail elderly patients. This paper aims at identif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 42 publications
0
6
0
Order By: Relevance
“…We find HRs between 3 and 10 (the largest possible for deciles) – indicating substantial risk stratification is possible with our approach. Our well-calibrated model provides accuracy in risk prediction results which would provide reliability for decision-making [34, 35]. Since we had calibrated probabilities, we also considered the distributions of transition probabilities.…”
Section: Discussionmentioning
confidence: 99%
“…We find HRs between 3 and 10 (the largest possible for deciles) – indicating substantial risk stratification is possible with our approach. Our well-calibrated model provides accuracy in risk prediction results which would provide reliability for decision-making [34, 35]. Since we had calibrated probabilities, we also considered the distributions of transition probabilities.…”
Section: Discussionmentioning
confidence: 99%
“…The WHO has highlighted the fundamental role of primary care in the management of patients with multimorbidity [3,7]. To guide this management, many countries use morbidity groupers to stratify populations according to complexity [8]. In Spain, the Adjusted Morbidity Groups (AMGs) have been developed within the Spanish healthcare system and are integrated into the electronic medical records of primary care [9].…”
Section: Introductionmentioning
confidence: 99%
“…The AMG grouper enables the measurement of multimorbidity to determine its impact on clinical-care management, epidemiology and healthcare administration, while also classifying patients into risk categories based on their morbidity and complexity [10]. This tool is useful for primary care professionals and policymakers, as it reveals the characteristics and use of services in patients with multimorbidity, serving as a guide to allocate healthcare resources efficiently and to plan appropriate care models and interventions based on each individual risk level, thereby successfully meeting the healthcare needs of patients with multimorbidity and efficiently managing healthcare services [8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…Criteria can be clinical (eg, medical conditions and complications) or non-clinical (eg, sociodemographic, household, environmental factors). Using these criteria, health providers categorise mother–baby dyads based on risk and proactively create client-specific care plans 10. A limited number of nascent programme experiences have provided initial results and lessons,11 buttressed by a review of PNHV approaches that identified the need for ‘specifically targeting high-risk mothers and newborns for PNHVs, rather than using a ‘blanket approach’ that attempts to reach all mothers and newborns’ 12.…”
Section: Introductionmentioning
confidence: 99%